Results from an experimental trial at a Head Start center to evaluate two meal service approaches to increase fruit and vegetable intake of preschool aged children - Harnack Lisa J; Oakes J; French Simone A; Rydell Sarah A; Farah Farhiyah M; Taylor Gretchen L (BMC, 2012)
Abstract Background Strategies to increase fruit and vegetable consumption of preschool aged children are needed. Objectives Evaluate the independent effects of the following meal service strategies on intake of fruits and vegetables of preschool children: 1.) Serving fruits and vegetables in advance of other menu items as part of traditional family style meal service; and 2.) Serving meals portioned and plated by providers. Methods Fifty-three preschool aged children completed a randomized crossover experiment conducted at a Head Start center in Minneapolis, MN. Over a six week trial period each of the experimental meal service strategies (serving fruits and vegetable first and serving meals portioned by providers) was implemented during lunch service for two one-week periods. Two one-week control periods (traditional family style meal service with all menu items served at once) were also included over the six week trial period. Childrens lunch intake was observed as a measure of food and nutrient intake during each experimental condition. Results Fruit intake was significantly higher (p<0.01) when fruits and vegetables were served in advance of other meal items (0.40 servings/meal) compared to the traditional family style meal service control condition when they were served in tandem with other menu items (0.32 servings/meal). Intakes of some nutrients found in fruits (vitamin A and folate) were concomitantly higher. In contrast, fruit and vegetable intakes were significantly lower and energy intake significantly higher during the provider portioned compared with control condition. Conclusions Serving fruits in advance of other meal items may be a low cost easy to implement strategy for increasing fruit intake in young children. However, serving vegetables first does not appear to increase vegetable intake. Results provide support for current recommendations for traditional family style meal service in preschool settings.